Academic Manuscript for the Draft of Village Regulation of Ploso Village, Wonoayu Subdistrict, Sidoarjo Regency, on Village Revenue Sources, Public Order, and Environmental Security - Afianto, Bagus; Phahlevy, Rifqi Ridlo (Indonesian Journal of Cultural and Community Development, 2024)
General Background: This study addresses the significant role of village regulations in managing revenue sources, public order, and environmental security, particularly in response to social and economic changes. Specific Background: The research focuses on the draft village regulation in Ploso, examining the current legal framework and its efficacy in addressing local challenges. Knowledge Gap: Despite existing literature on community engagement and regulation, there is a lack of research specifically analyzing the regulatory responses to ownership and security issues in rural settings. Aims: This study aims to assess the legal framework in place and recommend necessary regulatory updates to ensure effective management of public resources and community safety. Results: The findings indicate that challenges such as unclear land ownership of public facilities and increasing urbanization necessitate stricter regulations. The village administration's proactive approach, coupled with active community participation, is crucial for maintaining public order. Novelty: This research contributes to the understanding of local governance by highlighting the interplay between community participation and effective regulatory frameworks in rural areas. Implications: The study's insights underscore the importance of transparent and accountable governance, advocating for the development of clear regulations that align with current social dynamics and enhance community well-being, ultimately aiming for sustainable development in rural environments. Highlights: Proactive community engagement is essential for effective governance. Regulatory updates are necessary to address land ownership challenges. Transparent and accountable practices enhance community well-being. Keywords: Village Regulations, Public Order, Community Participation, Rural Governance, Sustainable Development